Perinatal Bisphenol A Exposure Beginning Before Gestation Enhances Allergen Sensitization, but Not Pulmonary Inflammation, in Adult Mice - O’Brien, Edmund (2014)
Bisphenol A (BPA), a monomer of polycarbonate plastics and epoxide resin, is a high-production-volume chemical implicated in asthma pathogenesis when exposure occurs to the developing fetus. However, few studies have directly examined the effect of in utero and early-life BPA exposure on the pathogenesis of asthma in adulthood. This study examines the influence of perinatal BPA exposure through maternal diet on allergen sensitization and pulmonary inflammation in adult offspring. Two weeks before mating, BALB/c dams were randomly assigned to a control diet or diets containing 50 ng, 50 μg, or 50 mg BPA/kg of rodent chow. Dams remained on the assigned diet throughout gestation and lactation until postnatal day 21 when offspring were weaned onto the control diet. Twelve-week-old offspring were sensitized to ovalbumin (OVA) and subsequently challenged with aerosolized OVA. Sera, splenocytes, bronchoalveolar lavage fluid, and whole lungs were harvested to assess allergen sensitization and pulmonary inflammation after OVA challenge. Serum anti-OVA IgE levels were increased 2-fold in offspring exposed to 50 μg and 50 mg BPA/kg diet, compared with control animals. In addition, production of IL-13 and IFN-γ were increased in OVA-stimulated splenocytes recovered from BPA-exposed mice. Pulmonary inflammation, as indicated by total and differential leukocyte counts, cytokines, chemokines, and pulmonary histopathology inflammatory scores, however, was either not different or was reduced in offspring exposed to BPA. While these data suggest that perinatal BPA exposure beginning before gestation enhances allergen sensitization by increasing serum IgE and splenocyte cytokine production, a substantial impact of BPA on OVA-induced pulmonary inflammation in adulthood was not observed.